A semi submerged habitat for the year 2100, in the context of a 5 meter sea level rise in Bangladesh - Hasan, Kazi Najeeb (BRAC Univeristy, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2015.